Une forme de recherche collaborative impulsée par les praticiens : enjeux, démarche, déplacement(s) des acteurs - Thérèse Perez-Roux
The article presents a form of collaborative research with new professionals from the school world: referent-teachers for school adaptation and schooling of pupils with special needs (ASH). The study deal with reflexivity, professional development, identity transactions of these professionals. Recognition issues and their relationship to forms of involvement in collaborative work are also discussed. The methodology, plural (focus group, sessions of analysis of practices, interviews, questionnaire), is long-termed. The results explicit a set of tensions identified within the collaborations between researchers and practitioners. They highlight a renewed approach to the complexity of actors, systems and work contexts. The study revisits the conditions for such collaboration, the postures of the various actors and the links between training, research and training that such a process allows to develop.